COVI-Prim international: Similarities and discrepancies in the way general practices from seven different countries coped with the COVID-19 pandemic - Siebenhofer, Andrea; Scott, Anna Mae; Avian, Alexander; Terebessy, András; Mergenthal, Karola; Schaffler-Schaden, Dagmar; Bachler, Herbert; Huter, Sebastian; Zelko, Erika; Murray, Amanda; Guppy, Michelle; Piccoliori, Giuliano; et al. (Frontiers in Public Health, 2022)
Objectives General practitioners (GPs) are frequently patients' first point of contact with the healthcare system and play an important role in identifying, managing and monitoring cases. This study investigated the experiences of GPs from seven different countries in the early phases of the COVID-19 pandemic. Design International cross-sectional online survey. Setting General practitioners from Australia, Austria, Germany, Hungary, Italy, Slovenia and Switzerland. Participants Overall, 1,642 GPs completed the survey. Main outcome measures We focused on how well-prepared GPs were, their self-confidence and concerns, efforts to control the spread of the disease, patient contacts, information flow, testing procedures and protection of staff. Results GPs gave high ratings to their self-confidence (7.3, 95% CI 7.1–7.5) and their efforts to control the spread of the disease (7.2, 95% CI 7.0–7.3). A decrease in the number of patient contacts (5.7, 95% CI 5.4–5.9), the perception of risk (5.3 95% CI 4.9–5.6), the provision of information to GPs (4.9, 95% CI 4.6–5.2), their testing of suspected cases (3.7, 95% CI 3.4–3.9) and their preparedness to face a pandemic (mean: 3.5; 95% CI 3.2–3.7) were rated as moderate. GPs gave low ratings to their ability to protect staff (2.2 95% CI 1.9–2.4). Differences were identified in all dimensions except protection of staff, which was consistently low in all surveyed GPs and countries. Conclusion Although GPs in the different countries were confronted with the same pandemic, its impact on specific aspects differed. This partly reflected differences in health care systems and experience of recent pandemics. However, it also showed that the development of structured care plans in case of future infectious diseases requires the early involvement of primary care representatives.